A exploração das máximas conversacionais de grice como estratégia argumentativa em charges e comentários no Instagram - Silva, Jucélia Azevedo dos Santos (2021)
The purpose of this research is to observe the relationship between the theory of implicatures (Grice (1982 [1975]) and argumentative approaches, with the aim of highlighting when Gricean conversational maxims are explored for persuasive purposes in the digital environment. It is noted that, each More and more, people use the digital environment as a space for interaction, whether to produce texts or to consume them. Therefore, in order to understand the use of language in this space, we propose, from a pragmatic perspective, to analyze interactions on the social network Instagram, which permeates different textual genres such as advertising, news, cartoons, comments, among others. To this end, we investigated two of these genres, published on the @laertegenial profile, which have an argumentative dimension: the cartoon and the comment. We analyzed 9 political cartoons, published between March and September 2019, and 53 comments. In both genres, we noticed that the violation of maxims occurred frequently and intentionally, to cause a certain effect on the interlocutors through implicatures, whether to criticize, denounce or persuade the other. We argue that Instagram often functions as an “arena” for public debate, as people are always interacting and positioning themselves. In the space reserved for comments, it is possible to observe these positions and how the debate takes place between users who take an argumentative stance. Furthermore, the information is conveyed not only explicitly, but, above all, implicitly. This means that, in the virtual environment, as well as in face-to-face interaction, people communicate using implicatures and, consequently, argue using implications. In addition to pragmatics, the analysis present in this work is based on studies by Koch (2018), Koch and Elias (2018), Fiorin (2020) and Amossy (2020), whose work proposals helped to understand how the language speaker produces his argumentation.